2021
DOI: 10.3390/cells10113043
|View full text |Cite
|
Sign up to set email alerts
|

Viral Membrane Fusion Proteins and RNA Sorting Mechanisms for the Molecular Delivery by Exosomes

Abstract: The advancement of precision medicine critically depends on the robustness and specificity of the carriers used for the targeted delivery of effector molecules in the human body. Numerous nanocarriers have been explored in vivo, to ensure the precise delivery of molecular cargos via tissue-specific targeting, including the endocrine part of the pancreas, thyroid, and adrenal glands. However, even after reaching the target organ, the cargo-carrying vehicle needs to enter the cell and then escape lysosomal destr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 202 publications
0
8
0
Order By: Relevance
“…This correlation might suggest a mechanism for lncRNAs to regulate exosome formation. RNA-binding proteins are involved in transferring RNA into exosomes [ 52 ]. We found that the modeling lncRNAs were extensively correlated with 1055 OS-related RBP genes.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation might suggest a mechanism for lncRNAs to regulate exosome formation. RNA-binding proteins are involved in transferring RNA into exosomes [ 52 ]. We found that the modeling lncRNAs were extensively correlated with 1055 OS-related RBP genes.…”
Section: Discussionmentioning
confidence: 99%
“…At that point, a refolding brings the two membranes in close contact and the fusion process can proceed towards the opening of a pore, passing through a hemifusion intermediate [49]. The insertion of a HA fusion peptide releases about 13 k B T , thus the action of three neighboring HA trimers is thought to generate enough energy to perturb the bilayer and overcome the dehydration barrier that keeps the two membranes apart [50], a task also accomplished by increasing the protrusion of lipid tails [51]. Thus, this energy released upon insertion can be used to move from the zeroth stage of fusion [38] to the following one.…”
Section: Discussionmentioning
confidence: 99%
“…There are different approaches to the classification of VLPs, depending on the presence of lipid envelopes (enveloped and non-enveloped) and on the form (helical, icosahedral, spherical, and complex) and the number of capsid layers (1, 2, and more). Small size, wide possibilities of surface modification, high biocompatibility, various ways of VLP production, the possibility of incorporating various chemicals inside—all these factors open up wide possibilities for the application of the virus-like particles, including the creation of vaccines, delivery of drugs, genes, proteins, and other chemicals [ 171 , 172 , 173 , 174 ].…”
Section: Protein-based Targeting Self-assembling Nanoparticles For Bi...mentioning
confidence: 99%